Heteroleptic iridium(iii) complexes bearing a coumarin moiety: an experimental and theoretical investigation1. Issue 96 (17th October 2015) - Maity, Amit; Sarkar, Rupa; Rajak, Kajal Krishna
<x xml:space="preserve">Abstract</x> Three mononuclear heteroleptic Ir(iii) complexes have been synthesized. The electronic structure and the spectral properties of the complexes were calculated applying the DFT-TDDFT method. The chemical shift was also computed by the GIAO-DFT method.